ONLINE BUSINESS COMPANY MARKETING STRATEGY MARKET SEGMENT GENERATION Z - Muh. Ridwansyah; Sampara Palili; Muhammad Tang (Proceeding of The International Conference on Economics and Business, 2022)
The discussion in this journal will focus on how the marketing strategy of online business companies in capturing market share, especially the Generation Z who dominates the world's population today. The digital economy concept is not much different from the general economic concept, but what distinguishes it is the transaction system in carrying out economic activities. The results of the study explain that online motorcycle taxi companies such as Gojek have the power as pioneers of online motorcycle taxi companies in Jakarta, this is a solution for Jakarta residents, especially Gen Z whose population is very dense so that the existence of Gojek will greatly assist Gen Z residents in meeting their needs, especially the costs involved. cheap according to the site www.aturduit.com. Gojek's weakness is a problem that must be resolved by the operator because it is related to the company's internals in this case is the "naughty" driver. Threats in the Gojek company are a classic thing faced by every business whose orientation is profit and finally the opportunity for Gojek according to the author is very large because the community's need is very high for mass transportation. Danaprospera.id's market segmentation includes investors, entrepreneurs and Gen z or young people who are productive and innovative. This is strongly supported by the commitment of online loan companies that are not burdensome in terms of bureaucracy according to the www.modalrakyat.id website.